A report of cerebellopontine angle epidermoid presenting with trigeminal neuralgia - Paramdeep Singh; Rupinderjeet Kaur; Rashmeet Kaur (Wolters Kluwer Medknow Publications, 2019)
Trigeminal neuralgia is typified by recurrent attacks of unilateral facial pain that is often severe and starts with cutaneous stimulation. These paroxysms usually last for few seconds, and the etiology comprises compression of the trigeminal nerve by vessels and space-occupying lesions of the brain and involvement by inflammatory plaques. It is rare for intracranial epidermoids to present as trigeminal neuralgia which is usually seen at the cerebellopontine angle, third ventricle, and suprasellar area and comprise about 1% of all intracranial tumors. We present the case of a 35-year-old male who had episodes of left-sided facial pain for the last few months. Magnetic resonance imaging revealed left cerebellopontine epidermoid which showed restriction on diffusion-weighted imaging and was operated upon. The symptoms completely resolved after the surgery.